Neuroacanthocytosis: a case report of chorea-acanthocytosis - Yuanyuan Xiang, Shan Li, Xiaohui Liu, Jifeng, Li, Qinjian, Sun, Yan, Chen, Yifeng Du, Junwei Wu (Journal of Integrative Neuroscience, 2019)
Neuroacanthocytosis is a rare progressive neurodegenerative disease, including chorea-acanthocytosis, McLeod syndrome, Huntington’s disease-like 2, and pantothenate kinase-associated neurodegeneration, where chorea-acanthocytosis occupies the main entity of this disease group. Here, a classic case of chorea-acanthocytosis is reported that exhibited gradually deteriorating abnormal movements of limbs and face, swallowing difficulty, and lip and cheek biting for the past two years. Peripheral blood smears revealed that 35% of the red blood cells were acanthocytes and electron microcopy scans clearly showed the morphology of acanthocytes. VPS13A gene sequencing found a heterozygous novel VPS13A gene mutation (c.80dupT). Brain magnetic resonance imaging scans showed moderate anterior horn dilation of lateral ventricles and bilateral atrophy of the head of caudate nucleus. Several suggestive features are summarized to provide diagnostic clues for chorea-acanthocytosis and facilitate future diagnosis and treatment.